2015
DOI: 10.1126/scisignal.aaa0899
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of eIF2α triggered by mTORC1 inhibition and PP6C activation is required for autophagy and is aberrant in PP6C-mutated melanoma

Abstract: Amino acid deprivation promotes the inhibition of the mammalian target of rapamycin (mTOR) kinase and activation of the general control nonrepressed-2 (GCN2) kinase. Signaling pathways downstream of both kinases have been thought to independently induce autophagy. Here we demonstrate that these two amino acid sensing systems are linked. We show that inhibition of mTORC1 leads to activation of GCN2 and phosphorylation of the eukaryotic initiation factor 2α (eIF2α) in a mechanism dependent on the PP6C phosphatas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
63
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 63 publications
8
63
3
Order By: Relevance
“…The downstream kinases of PI3K/AKT signalling pathway are thought to independently induce autophagy . Previous studies showed that pharmacological inhibition of the PI3K–AKT–mTOR signalling pathway led to phosphorylation of the eIF2α, which is a marker of ER stress, and our results are consistent with those findings.…”
Section: Discussionsupporting
confidence: 93%
“…The downstream kinases of PI3K/AKT signalling pathway are thought to independently induce autophagy . Previous studies showed that pharmacological inhibition of the PI3K–AKT–mTOR signalling pathway led to phosphorylation of the eIF2α, which is a marker of ER stress, and our results are consistent with those findings.…”
Section: Discussionsupporting
confidence: 93%
“…Although PP6 has an established role in TOR signaling in yeast [10], data confirming an analogous role in mammals has been scant. A recent report has linked PP6 to mTORC1 in the regulation of autophagy [13]. However, like our own results, these authors did not show that PP6 is directly responsible for the dephosphorylation of mTOR targets.…”
Section: Discussioncontrasting
confidence: 66%
“…However, Wengrod et al [13] recently showed that PP6 is required for the pharmacological induction of autophagy by pharmacologic inhibition of mTORC1, an action that also required GCN2 (general control nonrepressed 2) and eukaryotic initiation factor 2α (eIF2α). As noted above, PP6 has been implicated in the regulation of cell growth and proliferation, which may reflect its involvement in signaling by the mammalian homolog of the Target of Rapamycin, mTOR.…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical characterization found that these mutations are heterogeneous with regards to their effect on PP6c activity, stability, and subunit binding. Consequently, the mutant enzymes can function as loss-of-function tumor suppressors or gain-of-function oncoproteins (17, 18, 28). In glioblastoma, the abundance of PP6c is increased and negatively correlated with patient survival (29).…”
Section: Introductionmentioning
confidence: 99%